From Bergamo to Boston—5 Years Later: Autoethnography and the COVID Pandemic - Lori B. Lerner; Richard Naspro (COVID, 2025)
The COVID-19 pandemic was a worldwide crisis with significant impact on professional, economic, and social well-being. In medical academics, researchers were hampered by the need to provide critical support to pandemic efforts at their institutions, while balancing rapid communication of information that could impact practices and inform behavior. Autoethnography as a research method was employed by many early on as a means of characterizing aspects of the COVID-19 response. Two surgeons from heavily hit areas early in the epidemic—Bergamo, Italy, and Boston, the United States—entered into an online, virtual, professional relationship that helped them both endure the pandemic and inform their institutions and communities. Their relationship influenced practices across the United States and beyond. This paper explores how the principles of autoethnography as a valid, essential and important method of research can lead to significant impacts during times of crises.